Implementation of Government Agency Performance Accountability System in Tana Tidung District Government - Astuti, Deviyanti; Said, Moh; Muluk, Mujibu Rahman Khairul (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
This research is qualitative research with a case study approach. The purpose of this study is to evaluate SAKIP in Taha Tidung Regency Government which obtained a fixed SAKIP value. Descriptive analysis methods are used to evaluate SAKIP components, namely Performance Planning, Performance Measurement, Performance Reporting, Performance Evaluation and Performance Achievements. The results of the study on the evaluation of SAKIP Tana Tidung Regency show that the targeted accountability value has not increased significantly, tends to experience a slowdown, there are main problems that cause unsuccess, namely: a) performance as OPD has not been outcome oriented, and the performance indicators set have not fully met measurable, relevant, and reliable criteria, this affects the implementation Value for Money, and cascading of these achievements become less relevant and reliable; b) has not integrated the planning, management, and evaluation system in building performance management so as to describe the working relationship between work units / PD that is effective and efficient to produce the resulting performance.